Cultura, jurisdição e processo estrutural - Steffens, Luana (2021)
The main focus of this study is the the structural injunction as the proper tool for the protection of rights. As of the insertion of law as a cultural product, the evolution of the concept of adjutication in the contemporary State is analysed, as well as the origin and characteristics of the structural injunction and the challenges to which the reform is submitted. Founded in a deductive approach, the study begins with a brief input of the cultural influence on Law and procedure, and also its effects on adjudication and Constitutional State. After the new face of adjutication and the insufficiency of procedural tools to handle complex disputes are demonstrated in contemporary times, there is a need of a new procedural technique to handle these conflicts, which is the structural procedural technique. Based on this assumptions, the notion of structural procedure is approached and the obstacles and controversies related to this procedure model. Some comparative law precedents are analysed and essential characteristics of a structural process are examined. Finally, as the new litigation model and the proper procedural tool are identified, the current challenges of the structural procedure are examined, noticeably regarding the necessary arrangement to adapt the procedure to a new reality, consisting of complex disputes and/or public interest. In conclusion, the structural injunction is the most adequate tool to reach the protection of rights in complex litigation, seeing they the procedure, the dialogical opening and participation, as well as the particular actions of the judge in this model.